A Visible–Near‐Infrared Light‐Responsive Host–Guest Pair with Nanomolar Affinity in Water. Issue 14 (12th February 2019) - Ferreira, Pedro; Ventura, Barbara; Barbieri, Andrea; Da Silva, José P.; Laia, César A. T.; Parola, A. Jorge; Basílio, Nuno
Abstract: The discovery of stimuli‐responsive high affinity host–guest pairs with potential applications under biologically relevant conditions is a challenging goal. This work reports a high‐affinity 1:1 complex formed between cucurbit[8]uril and a water‐soluble photochromic diarylethene derivative. It was found that, by confining the open isomer within the cavity of the receptor, a redshift in the absorption spectrum and an enhancement of the photocyclization quantum yield from Φ =0.04 to Φ =0.32 were induced. This improvement in the photochemical performance enables quantitative photocyclization with visible light that, together with the near‐infrared light‐induced ring‐opening reaction and the 100‐fold selectivity for the closed isomer, confirms this as an outstanding light‐responsive affinity pair. Abstract : A water‐soluble photochromic diarylethene derivative forms 1:1 host–guest complexes with cucurbit[8]uril. Remarkably, the closed isomer shows nanomolar affinity for the macrocyclic receptor, whereas for the open isomer the binding constant decreases by two orders of magnitude. This differential binding affinity confers light‐responsive properties to the host–guest system, allowing remote control over the association/dissociation process in the nanomolar concentration range and photoregulation of the complexation of classic high‐affinity pairs through competitive binding.